Ludicity and dyslexia: a teaching proposal with a student of Youth and Adult Education (EJA) - Jarbas de Negreiros Pereira; Gabriela de Aguiar Carvalho (Universidade Federal do Oeste da Bahia, 2021)
The application of games is extremely substantial, as it constitutes a didactic factor, considered a favorable element for the teaching-learning process for those who intend to motivate their students to teach. The objective of this work was to reflect on the relationship and influence of the game in the learning of a student of EJA with dyslexia. The game consists of a board, a dice, two pins, six packets of letters and a crossword. As a result, he got 4 words right on the 1st try and 2 words on the 2nd try. In the case of the dictation, with eight words, the student got 3 words right on the 1st attempt. Therefore, there is a positive and promising evaluation, if there is continuous pedagogical work on the part of their teachers, the student will have a great potential for growth in linguistic competence.